Conversaciones tempranas: comunicación y diálogo - Reddy, Vasudevi (Acción Psicológica, 2012)
Abstract What is dialogue and how can we find it? This paper addresses this question in the context of tracing the origins of communication in human infancy. Structural criteria - such as turn taking -have often been used to identify genuine communication. Implementing these criteria have led to considerable debate in relation to the ’proto-conversations’ of the twomonth- old, debates which arose in the late 1970s and are still alive today. The paper considers some of the evidence from infant behaviour involved in these debates and in relation to the question of infants’ awareness of the ’meaning’ of adult facial expressions. In addition to these structural criteria it is suggested that functional criteria such as openness and recognition might be important for our understanding of the origins of dialogue. The paper discusses the apparent paradox of language -how communication is needed to make private experience public, but at the same time, cannot occur until experience is already public- and argues that this paradox disappears if shared experience rather than private representation is taken as primary.